Reframing Holocaust testimony - Shenker, Noah (The modern Jewish experience, 2015)
1. Testimonies from the Grassroots: The Fortunoff Video Archive for Holocaust Testimonies -- 2. Centralizing Holocaust Testimony: The United States Holocaust Memorial Museum -- 3. The Cinematic Origins and the Digital Future of the Shoah Foundation -- 4. Telling and Retelling Holocaust Testimonies. Conclusion: Documenting Genocide through the Lens of the Holocaust